2020
DOI: 10.1016/j.gca.2020.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of sulfur between solid and liquid iron under Earth’s core conditions: Constraints from atomistic simulations with machine learning potentials

Abstract: Partition coefficients of light elements between the solid and liquid iron phases are crucial for uncovering the state and dynamics of the Earth's core. As one of the major light element candidates, sulfur has attracted extensive interests for measuring its partitioning and phase behaviors over the last several decades, but the relevant experimental data under Earth's core conditions are still scarce. In this study, using a toolkit consisting of electronic structure theory, high-accuracy machine learning poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 78 publications
1
47
0
Order By: Relevance
“…If the mass fraction of light elements in the core is χ S , the core's bulk density (neglecting compression, which is discussed in Section 2.2) is given by 1ρnormalc=1χnormalSρFe+χnormalSρnormalS where we use the subscript S because we assume sulfur to be the principal light element species in the Martian core (Franz et al., 2019; Gaillard & Scaillet, 2009), and where ρ Fe and ρ S are the densities of the major and minor species (assumed to be iron and sulfur), respectively. Neglecting the small density differences between the solid and liquid forms of both the major and minor species (i.e., assuming ρ Fe, sol = ρ Fe, liq = 6,980 kg/m 3 and ρ S,sol = ρ S,liq = 1,819 kg/m 3 ), we can approximate the light element‐enriched liquid density using 1ρχ=1χS,liqρFe+χS,liqρnormalS where, assuming small control volumes partition into equal parts solid and liquid by mass, it can be shown that χS,liq=21+DnormalSχnormalS is the mass fraction of light elements in the residual liquid, where D S is the solid‐liquid phase partitioning coefficient for the light elements (i.e., the mole fraction of light elements that partition into the solid phase vs. the liquid phase) (Zhang et al., 2020). Note that if sulfur partitions into the solid and liquid phases in equal proportions (i.e., if D S = 1), then ρ χ remains the same as the bulk core density and Δ ρ χ = 0; if sulfur partitions preferentially into the liquid, then D S < 1 and ρ χ < ρ c so the residual liquid is positively buoyant.…”
Section: Methodsmentioning
confidence: 99%
“…If the mass fraction of light elements in the core is χ S , the core's bulk density (neglecting compression, which is discussed in Section 2.2) is given by 1ρnormalc=1χnormalSρFe+χnormalSρnormalS where we use the subscript S because we assume sulfur to be the principal light element species in the Martian core (Franz et al., 2019; Gaillard & Scaillet, 2009), and where ρ Fe and ρ S are the densities of the major and minor species (assumed to be iron and sulfur), respectively. Neglecting the small density differences between the solid and liquid forms of both the major and minor species (i.e., assuming ρ Fe, sol = ρ Fe, liq = 6,980 kg/m 3 and ρ S,sol = ρ S,liq = 1,819 kg/m 3 ), we can approximate the light element‐enriched liquid density using 1ρχ=1χS,liqρFe+χS,liqρnormalS where, assuming small control volumes partition into equal parts solid and liquid by mass, it can be shown that χS,liq=21+DnormalSχnormalS is the mass fraction of light elements in the residual liquid, where D S is the solid‐liquid phase partitioning coefficient for the light elements (i.e., the mole fraction of light elements that partition into the solid phase vs. the liquid phase) (Zhang et al., 2020). Note that if sulfur partitions into the solid and liquid phases in equal proportions (i.e., if D S = 1), then ρ χ remains the same as the bulk core density and Δ ρ χ = 0; if sulfur partitions preferentially into the liquid, then D S < 1 and ρ χ < ρ c so the residual liquid is positively buoyant.…”
Section: Methodsmentioning
confidence: 99%
“…As an example of an application at the other extreme of the temperature and pressure scale (where magnetism is suppressed), a GAP was developed to study liquid iron and sulfur under conditions corresponding to those at the Earth’s core: temperatures ranging from 4000 to 7000 K and pressures between 110 and 430 GPa. 248 One of the objectives of that work was to study the partition coefficient of sulfur between solid and liquid iron. The GAP model reproduced the radial distribution functions of Fe, S, and Fe–S with high fidelity with respect to a DFT reference, as well as the melting curve of Fe.…”
Section: Applications (I): Force Fieldsmentioning
confidence: 99%
“…The emerging use of machine-learning methods was also illustrated in two contributions that parameterize atomic scale simulations, and upscale geomaterials microscopic properties to continuum-scale modeling. Finally, the topics explored in these contributions span a wide range of geochemical topics applicable to environments from the Earth's core to its surface, including: solid-liquid partitioning under Earth's core conditions (Zhang et al, 2020b), chemical geodynamics of the mantle (Zhang and Liu, 2020), recycling of noble gas in the subduction zones (Wang et al, 2020), thermodynamics of hydrothermal fluids (Mei et al, 2020), interfacial and structural properties of clay and (Fe, Mn) oxide materials (Bylaska et al, 2020;Newton and Kwon, 2020;Zhang et al, 2020a), and a machine learning-based framework for coupling and upscaling of reactive transport processes and parameters across spatial scales (Prasianakis et al, 2020). These papers are briefly introduced in the following.…”
Section: Preface To Multiscale Simulation In Geochemistrymentioning
confidence: 99%
“…Sulfur is one of the major candidates for the light elements in the Earth's core and its partitioning across the inner core boundary may be important to drive the magnetic field related convection in the outer core. To obtain the accurate partition coefficients of sulfur under Earth's core conditions, which is still unclear from experiments, Zhang et al (Zhang et al, 2020b) present a new framework based on a machine learning approach trained on high quality quantum mechanics data. By extending the data to higher T-P conditions unavailable with current experimental approaches, they show that the partition coefficient of sulfur is essentially insensitive to temperatures and pressures.…”
Section: Preface To Multiscale Simulation In Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation